تأثير زاوية ورود الأمواج في المرشح التجزيئي الميكروي - سرحيل, فاتن (Latakia University Journal -Engineering Sciences Series, 2014)
دﹸرست المرشحات التي تعتمد على البنى التجزيئية سابقاً وتم تحليل التأثير الناجم عن معاملات البنى التجزيئية في تصميم المرشح , وذلك بافتراض ورود الأمواج بشكل ناظمي , بينما يقدم هذا البحث دراسة حول تأثير ورود الأمواج بشكل مائل في تصميم المرشحات التجزيئية , إذ اخترنا الشريط الكانتوري (Cantor bar) كنموذج عن البنى التجزيئية(Fractals) , حيث نناقش أولاً معاملات الإرسال والانعكاس عنه عند ورود الأمواج الكهرطيسية بشكل مائل, ثانياً نرسم مخططات الانعراج (twist plots)التي تنطلق منها عملية تصميم المرشحات التجزيئية الانتقائية, أخيراً نبرهن أن انحراف الأمواج بمقدار بسيط لا يكون له تأثير ملحوظ في المرشح التجزيئي. Fractal filters have been studied before, and the effect of fractal parameters on the design of filter has been discussed for normal incident. In this paper, we propose a study for the effect of the angle of incidence on fractal filters. We choose a Cantor bar as an example of fractals. Firstly, we investigate its reflection and transmission coefficients when an electromagnetic wave obliquely occurs. Secondly, we draw twist plots which can be help design selective fractal filters. Finally, we demonstrate that the little deviation of the wave incident angle gives very small changes in terms of resonant frequency and bandwidth of fractal filters.